An enlarging scaly plaque localized on the previous keloid of the chest - Amir Houshang Ehsani; Kambiz Kamyab‐Hesari; Pedram Noormohammadpour; Hamidreza Mahmoudi; Zahra Razavi (Clinical Case Reports, 2020)
Abstract Mycosis fungoides (MF) is the most common type of cutaneous T‐cell lymphoma (CTCL). It may arise rapidly in a scar or keloid, presumably due to a long‐standing proliferative state or autoimmune theory. There should be a low threshold for performing a skin biopsy if unusual lesions develop at those sites.